ANALISIS STRATEGI MANAJEMEN RESTO DAPUR JOGLO DALAM MENCIPTAKAN KEPUASAN PELANGGAN DAN MEMPERKUAT POSISI INDUSTRI KULINER - Ririn, Ririn Fatmawati; Sherly, Sintya Gadis; Novia, Risma; Sari, Lisa (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
The rapid growth of the culinary industry in Indonesia has intensified competition, particularly for traditional restaurants like Resto Dapur Joglo, which must compete with modern and fast-food establishments while adapting to the trend of digitalized food services. This study aims to analyze the management strategies of Resto Dapur Joglo in creating customer satisfaction and strengthening its position in the culinary industry, with a focus on optimizing internal strengths and leveraging external opportunities. The method used is a case study with a descriptive qualitative approach, conducted through observation, interviews, customer questionnaires, and documentation. Data were analyzed using the SWOT matrix, IFAS, and EFAS to identify the strengths, weaknesses, opportunities, and threats faced by the business. The analysis results show that Resto Dapur Joglo’s main strengths lie in its comfortable atmosphere, quality flavors, and personalized service (IFAS strength score: 2.35), along with significant opportunities in online service digitalization and business expansion (highest EFAS score: 0.54). The IFAS score difference of 1.32 and EFAS of 0.31 place Resto Dapur Joglo in the aggressive strategy position (SWOT quadrant I), thus it is recommended to maximize existing strengths and opportunities through menu innovation, digital promotion, and operational cost efficiency to face competition and enhance customer satisfaction.